Prevalence and genotype distribution of high-risk Human Papillomavirus infection among Vietnamese women in Ho Chi Minh City, Viet Nam: A population-based cross-sectional study - Ho Minh Nguyet; Phan Thanh Tam; Quach Kim Ung; To Gia Kien; Le Hong Phuoc (Gynecologic Oncology Reports)
Introduction: Persistent infection with high-risk Human Papillomavirus (HR-HPV) genotypes are wellknown to increase the risk of cervical cancer significantly. This study aims to determine the prevalence and distribution of high-risk HR-HPV genotypes among women in Ho Chi Minh City (HCMC), Viet Nam. Methods: A population-based cross-sectional study was conducted between June 2020 and September 2020 in all 24 districts of HCMC, Viet Nam. Socio-demographic and behavioral data were collected from 2478 women aged 25 to 65 who had sexual intercourse using a self-administered questionnaire. Vaginal swab specimens from all participants were collected to identify HR-HPV genotypes using Polymerase Chain Reaction (PCR) protocols. Results: The prevalence of HR-HPV infection was 3.5 % (87 women, including 20 cases infected with multi-genotypes), 3.1 % in urban and 0.4 % in rural areas. The most detected HR-HPV genotypes among positive cases were 58 (25.3 %), 52 (21.8 %), 16 (21.8 %), 68 (10.3 %), 51 (10.34 %) and 18 (9.2 %). The prevalence of multi-type HR-HPV genotypes was 0.81 %, of which the most common co-infection genotypes were 52 and 58 (20.0 %), 16 and 56 (10.0 %), and 16 and 39 (10.0 %). The percentages of one-, two-, three-, and four-genotypes of HPV among positive cases were 77.0 %, 16.1 %, 4.6 % and 2.3 %, respectively. Conclusions: Our findings explore a low prevalence of HR-HPV infection in Vietnamese women, of which genotypes 52 and 58 are more popular than 16 and 18. Continuously updated data on the genotype distribution of HPV are helpful for vaccine development and planning preventive activities to prevent HPV-related cancers.